2023
DOI: 10.3390/ijms242316555
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Proliferative Potential of Cynaroside and Orientin—In Silico (DYRK2) and In Vitro (U87 and Caco-2) Studies

Lucia Camelia Pirvu,
Lucia Pintilie,
Adrian Albulescu
et al.

Abstract: Luteolin derivates are plant compounds with multiple benefits for human health. Stability to heat and acid hydrolysis and high resistance to (auto)oxidation are other arguments for the laden interest in luteolin derivates today. The present study was designed to compare the in silico and in vitro anti-proliferative potential of two luteolin derivates, luteolin-7-O-glucoside/cynaroside (7-Lut) and luteolin-8-C-glucoside/orientin (8-Lut). In silico investigations were carried out on the molecular target, namely,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
1
0
0
Order By: Relevance
“…Regarding the flavonoids tested, one study indicated that exposing Caco-2 cells to L-7-G, for 48 h, significantly reduces cell viability to 50% of control, at ~55 µM [27], a value much lower than the one here presented (Figure 2C). Another study reported a 38% reduction in the viability of Caco-2 cells exposed for 24 h to 223 µM L-7-G [28], a value similar to that presented in Figure 2C. L-7-G was shown to reduce HepG2 cells' viability to ~50% at 44.60 µM [29], a value also lower than the one here reported (Figure 2K).…”
Section: Safety Profile Of T Carnosus Extracts and Their Main Phytoch...supporting
confidence: 79%
“…Regarding the flavonoids tested, one study indicated that exposing Caco-2 cells to L-7-G, for 48 h, significantly reduces cell viability to 50% of control, at ~55 µM [27], a value much lower than the one here presented (Figure 2C). Another study reported a 38% reduction in the viability of Caco-2 cells exposed for 24 h to 223 µM L-7-G [28], a value similar to that presented in Figure 2C. L-7-G was shown to reduce HepG2 cells' viability to ~50% at 44.60 µM [29], a value also lower than the one here reported (Figure 2K).…”
Section: Safety Profile Of T Carnosus Extracts and Their Main Phytoch...supporting
confidence: 79%